2021
DOI: 10.3390/ijms221910447
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Role of NLRP3 Inflammasome in Viral Infection-Associated Fibrosing Interstitial Lung Diseases

Abstract: Idiopathic pulmonary fibrosis (IPF), one of the most common fibrosing interstitial lung diseases (ILD), is a chronic-age-related respiratory disease that rises from repeated micro-injury of the alveolar epithelium. Environmental influences, intrinsic factors, genetic and epigenetic risk factors that lead to chronic inflammation might be implicated in the development of IPF. The exact triggers that initiate the fibrotic response in IPF remain enigmatic, but there is now increasing evidence supporting the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 122 publications
0
8
0
Order By: Relevance
“…Later, investigators found that inflammation is involved in different stages of IPF development due to the activation of the innate and adaptive immune systems [6][7][8]. Environmental influences and genetic risk factors leading to chronic inflammation may be associated with the development of IPF [9]. C-reactive protein (CRP) is often considered a marker of the inflammatory response in the acute phase.…”
Section: Introductionmentioning
confidence: 99%
“…Later, investigators found that inflammation is involved in different stages of IPF development due to the activation of the innate and adaptive immune systems [6][7][8]. Environmental influences and genetic risk factors leading to chronic inflammation may be associated with the development of IPF [9]. C-reactive protein (CRP) is often considered a marker of the inflammatory response in the acute phase.…”
Section: Introductionmentioning
confidence: 99%
“…As a core protein, activated NLRP3 recruits the downstream proteins ASC and procaspase-1 to cause maturation and secretion of the highly proinflammatory cytokines IL-1β and IL-18 [35]. NLRP3 inflammasome activation is also observed in pulmonary fibrosis models induced by asbestos, silica and bleomycin, and pulmonary fibrosis is alleviated by the inhibition of NLRP3 inflammasome activation [36][37][38]. Our results are in agreement with the results of previous studies, showing that NecroX-5 significantly inhibited NLRP3 inflammasome activation in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the activation of the NLRP3 inflammasome by integrating multiple cellular and molecular signaling implicates robust fibroblast proliferation with activation of myofibroblast, matrix deposition, and aberrant epithelial–mesenchymal function. And, the NLRP3 inflammasome may trigger the release of the proinflammatory cytokines such as interleukin (IL)-1β, IL-6, and IL-18 and initiate or exacerbate the HD ( 2 , 3 ). The rate of virus infection in the ILD-IPF is high ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%